(untitled) (Вісник: Міжнародні відносини, 2021)
The article examines current global trends in digital marketing, namely digital technologies such as hyperautomation, artificial intelligence, augmented and virtual reality, Internet of Behaviors, Big Data. Particular attention is paid to web analytics tools and the practice of their application in analyzing consumer behaviour in international business. Today, marketing is developing in the direction of technological and cognitive industries, it will develop IT solutions that allow companies to analyze large amounts of information in a short period, structure them and develop business strategies on this basis. For example, Big Data helps analyze different types of data such as static – personal information with demographics, realtime – geolocation, and transaction history, and behavioural – actions on third-party sites and social networks, as well as forecast the results of strategic decisions. The most famous web analytics systems are Google Analytics and Yandex.Metrica. Google Analytics makes it easy to analyze behavioural metrics, improve the quality of a resource or digital advertising, and promote effective online promotion. Yandex.Metrics and its tool Webvisor allows a company to view user actions in video mode: mouse cursor movements, clicks, scrolling, filling out forms, which helps to find problem areas in the use of the website and better understand the behaviour of visitors. The article also considers various technical, quantitative and qualitative tools of web analytics, which can be used to analyze site data for certain parameters, eliminate possible errors in the structure, make it more convenient for visitors, formulate a marketing strategy.